Design improvements and flap deflection evaluations with considering centrifugal load on active trailing edge flap. Issue 1 (13th November 2018) - Visconti, Umberto; Eun, WonJong; Sim, JiSoo; Lee, SangWoo; Shin, SangJoon
Abstract : Purpose: The purpose of this paper is to present the design, analysis and experiments of the active trailing-edge flap (Seoul National University Flap, SNUF) for vibration reduction in the helicopter rotor prior to the small-scale blades planned to test in a whirl tower. Design/methodology/approach: The predictions of the hinge moment in both steady and unsteady flows were obtained through computational fluid dynamics calculations. When compared with the results originated from analytical formulations, the proposed method showed improved prediction capabilities. To validate the deflection of the flap under the centrifugal load by rotating, static analysis was conducted using both contact and rotating condition of MSC NASTRAN. The corresponding experiment also was performed using the vertical frame for simulating the effect of the centrifugal force. Findings: The hinge moment of the flap is predicted through unsteady analysis in the actuation frequency of 3/rev. The material of the guide in the flap mechanism was selected through static analysis under both contact and rotating condition. Finally, reduction of the deflection occurred because of the load in the axial direction of the hinge like the centrifugal load. Practical implications: The important aspects, such as design, analysis, and experiments for the active trailing-edge flap were shown. Originality/value: This paper showed the relationship of the displacement, block force and voltage of the piezo-actuator, combined with the hinge moment predicted. The methodology and the experiment were presented for simulating the centrifugal force acting on the flap.